A leitura na escola : concepções de professores de diferentes disciplinas das séries finais do Ensino Fundamental. - Silva, Maria Vitoria da (2007)
In the exercise of the teaching, teachers of the Final Series of the Fundamental Teaching have come across a significant amount of students that doesn't present necessary basic reading abilities for the learning of specific contents of the several disciplines. In that perspective, we brought up the following research question which guided the present work: How do the teachers of several disciplines of the Fundamental Teaching final series conceive the reading and its teaching? To answer to that questioning we figured out as general objective, to understand the reading conceptions that permeate the teacher's pedagogic practice of the several disciplines of the Fundamental Teaching final series. The theoretical referential is ruled in the studies of Imbernón, Pacheco and Flores, Nóvoa and Mizukami, which have been pointing important contributions for the debate and construction of knowledge on the educational formation and the teacher's professional development and also in the studies of Chartier, Kleiman, Silva, Solé, which conceive the reading as a continuous process, complex and plural, supplying important contributions for its discussion in the education field. The methodological procedures were orientated by the principles of the qualitative research in education, especially the valorization of the teachers' voice, trying to understand their conceptions, their knowledge and faiths as basis of their work with the teaching. As data collection instruments were used the semi-structured interview and the analysis of written materials (course plans, class script and written activities). Five experienced teachers of the disciplines Sciences, Geography, History, Mathematics and Portuguese took part in the research. They teach from 5th to 8th series of the Fundamental Teaching at a school located in the rural area of the municipal district of Feira de Santana, Bahia. The collected data were contained into five analysis dimensions, that is, reading definition, school and reading relationship, reading and specific content relationship, the student's relationship with the reading and the teaching process and reading learning in different disciplines. As result, is possible to stand out that the teachers present in the most conceptual dimensions, a wide, continuous and dynamic conception about the reading. In the dimensions that involve the student and the classroom, a certain distance is verified between what they speak and what the theory proposes. However, it is noticed in the practices reported by the teachers, indications of a search movement for innovation of the daily practices. They recognize the need of the group work involving the whole school around the learning of the reading. We stand out the continuous formation that happens in the exercise of the teaching and in the group work in the school, as a possibility for the teacher to build strategies that contribute with the student's development in what refers to a competent reader's abilities.